development of University Innovative Potential as a Factor Contributing to the Growth of Labor Satisfaction of Young Teachers - N. I. Prokopov; S. N. Antonyuk; S. Yu. Ivanov; D. V. Ivanova (Высшее образование в России)
Based on the results of the authors’ sociological research, the article analyzes the components that determine the professional development trajectories of young teachers in an innovative technical University. In the course of studying the respondents’ motivational preferences and working conditions there were revealed the peculiarities of young teachers’ adaptation in the educational process. The requirements imposed by the University in the process of its innovative development on young teachers and researchers are of key importance. An openness of the University to innovation involves the formation of a whole range of activities on quality management, measuring the activity of young teachers in research and educational work of structural units. The presented complex analysis of the developing practices allows to reveal the most “bottlenecks” in the work with young people and to offer a list of practical recommendations for the fuller use of their professional potential.